IEAP Initiative Status Report Spring 2023 (2023)
Critical Learning Collectives (CLCs), initially called Critical Friends Groups (CFGs) in earlier iterations at CSUCI, are professional learning communities that strive to create a safe space for learning and problem-solving where risk-taking is possible and discomfort is valued, where courageous questions about our respective challenges as faculty, staff, and administrators can be asked and methodically examined by "critical friends," and where possibilities for resolution can be generated by first taking care to study available data—ensuring that understanding of any given problem or dilemma precedes recommendations, decisions, and actions taken.CLCs are not spaces for griping about problems. A CLC that spends any time in this way is missing the intention and spirit of these groups. CLC discussions are guided by structured protocols to protect against participants being tempted to use precious shared time for mere complaint, or worse, to breakconfidentiality about any individual participant's confidence who shared their perspective about any particular problem or dilemma being worked on within the group.